The importance of the Thr17 residue of phospholamban as a phosphorylation site under physiological and pathological conditions - Mattiazzi, Alicia Ramona (2006)
The sarcoplasmic reticulum (SR) Ca2+-ATPase (SERCA2a) is under the control of an SR protein named phospholamban (PLN). Dephosphorylated PLN inhibits SERCA2a, whereas phosphorylation of PLN at either the Ser16 site by PKA or the Thr17 site by CaMKII reverses this inhibition, thus increasing SERCA2a activity and the rate of Ca2+ uptake by the SR. This leads to an increase in the velocity of relaxation, SR Ca2+ load and myocardial contractility. In the intact heart, β-adrenoceptor stimulation results in phosphorylation of PLN at both Ser16 and Thr17 residues. Phosphorylation of the Thr17 residue requires both stimulation of the CaMKII signaling pathways and inhibition of PP1, the major phosphatase that dephosphorylates PLN. These two prerequisites appear to be fulfilled by β-adrenoceptor stimulation, which as a result of PKA activation, triggers the activation of CaMKII by increasing intracellular Ca2+, and inhibits PP1. Several pathological situations such as ischemia-reperfusion injury or hypercapnic acidosis provide the required conditions for the phosphorylation of the Thr17 residue of PLN, independently of the increase in PKA activity, i.e., increased intracellular Ca2+ and acidosis-induced phosphatase inhibition. Our results indicated that PLN was phosphorylated at Thr17 at the onset of reflow and immediately after hypercapnia was established, and that this phosphorylation contributes to the mechanical recovery after both the ischemic and acidic insults. Studies on transgenic mice with Thr17 mutated to Ala (PLN-T17A) are consistent with these results. Thus, phosphorylation of the Thr17 residue of PLN probably participates in a protective mechanism that favors Ca2+ handling and limits intracellular Ca2+ overload in pathological situations.